2014
DOI: 10.1021/ct500680q
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ionic Strength in Biomolecular Simulations of Charged Lipid Bilayers

Abstract: Biological membranes are complex systems that have recently attracted a significant scientific interest. Due to the presence of many different anionic lipids, these membranes are usually negatively charged and sensitive to pH. The protonation states of lipids and the ion distribution close to the bilayer are two of the main challenges in biomolecular simulations of these systems. These two problems have been circumvented by using ionized (deprotonated) anionic lipids and enough counterions to preserve the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(96 citation statements)
references
References 104 publications
11
83
2
Order By: Relevance
“…30,68 Lipid14, together with the various AMBER ion parameters, is no exception in that regard. Monovalent counterions described by parameters recently developed by Joung and Cheatham 69 have been found to condense anionic Lipid14 bilayers to areas per lipid well below experimental values (results not shown) due to strong interactions with the negatively charged lipid head groups.…”
Section: Resultsmentioning
confidence: 99%
“…30,68 Lipid14, together with the various AMBER ion parameters, is no exception in that regard. Monovalent counterions described by parameters recently developed by Joung and Cheatham 69 have been found to condense anionic Lipid14 bilayers to areas per lipid well below experimental values (results not shown) due to strong interactions with the negatively charged lipid head groups.…”
Section: Resultsmentioning
confidence: 99%
“…Titratable water was used to maintain constant charge throughout the simulations for all pH conditions. 24,25 Recent work from other groups showed that the number of counter-ions required to neutralize a simulation box may result in an artificially high concentration of ions near a charged solute, 39 and that high ion concentrations can possibly lead to artifacts. 40 However, since the potential artifacts affect the morphology of lipid and surfactant assemblies, which is not the topic of this work, we feel that the charge neutralization scheme used here is appropriate, especially given that our recent work showed that enforcing charge neutrality in the simulation box significantly improves the accuracy of all-atom constant pH MD simulations.…”
Section: Methodsmentioning
confidence: 99%
“…In one of them, we kept the Berger lipids/HF 6-31G(d) probe topologies used in the main set of simulations, but added sodium and chloride ions to a physiological (150 mM) ionic strength. It should be stressed that possibly owing to the relatively small simulation boxes (namely in the direction normal to the bilayer plane) that may be presently addressed in atomistic MD, as well as to uncertainty in the force field parameters of common ions, the number of cations in close vicinity of the bilayer is overestimated in the conventional MD simulation protocols [98][99][100]. In turn, this leads to an overestimation of ion-induced alterations of host lipid properties.…”
Section: Probe Rotational and Lateral Diffusionmentioning
confidence: 99%